'Change the Heart, and the Work Will Be Changed': Pius XII's Papal Blueprints for Europe. (February 2022) - Lanting, Dorien; Palm, Trineke
Abstract : This article examines the role of emotions in papal discourse about European integration. Expanding on the 'emotional turn' in history, it develops an analytic framework to study emotional valence in constructing the past and future. Analysing Pope Pius XII's three major post-war encyclicals ( Communium Interpretes Dolorum, Fulgens Radiatur and Summi Maeroris ), this article shows how the emotional vocabulary of Pius XII bridges the gap between theology and politics. In particular, it illuminates how Pope Pius XII integrated emotional and religious vocabulary to (re)construct an image of a European past and future.